2009
DOI: 10.1590/s0004-282x2009000600007
|View full text |Cite
|
Sign up to set email alerts
|

Does sudden unexpected death in children with epilepsy occur more frequently in those with high seizure frequency?

Abstract: -People with epilepsy are more likely to die prematurely and the most common epilepsy-related category of death is sudden unexpected death in epilepsy (SUDEP). Several studies have reported a moderate or high seizure frequency among SUDEP cases and SUDEP is considered rare in patients in remission. Method: We reviewed the occurrence of SUDEP in our epilepsy unit over an 8-year period to identify a potential association between seizure frequency and SUDEP occurrence in children with epilepsy. Results: From 835 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 6 publications
1
22
0
Order By: Relevance
“…A recent longitudinal study that followed children with epilepsy undergoing pharmacologic treatment over several years concluded that "SUDEP is not a rare event in children" (Terra et al 2009). As 1.4% of the subjects succumbed to SUDEP during the study, the authors noted that premature mortality rates associated with SUDEP could diminish if more pediatric research were conducted.…”
mentioning
confidence: 99%
“…A recent longitudinal study that followed children with epilepsy undergoing pharmacologic treatment over several years concluded that "SUDEP is not a rare event in children" (Terra et al 2009). As 1.4% of the subjects succumbed to SUDEP during the study, the authors noted that premature mortality rates associated with SUDEP could diminish if more pediatric research were conducted.…”
mentioning
confidence: 99%
“…Although few data exist about the risk of SUDEP in children, a recent study by our research group demonstrated that increased SUDEP occurrence appeared in children unresponsive to antiepileptic therapy, with no increase in risk observed in patients who remained seizure free 31 . An additional important issue is evidence that phenytoin can exert toxic effects on the cerebellum in patients with epilepsy 32 ; the toxicity is associated with ataxia, tremor, nystagmus and diplopia 32,33 .…”
Section: Brain Regions and Sudepmentioning
confidence: 80%
“…Briefly, from the 835 patients evaluated, 12 had suffered SUDEP and nearly all of the SUDEP cases in our children were related to chronic uncontrolled epilepsy (daily -50.0%, two to four/weeks -41.7%, monthly -8.3%). Furthermore, the high frequency of generalized tonic-clonic seizures and polytherapy with antiepileptic drugs may also be highlighted as risk factors in our study 19 . By assessing the information set out so far and considering that although the availability of pharmacological and surgical treatment for epilepsy has expanded, antiepileptic drugs and some resective procedures are still limited in clinic efficacy.…”
mentioning
confidence: 83%
“…According to the excellent review article published recently by Sascha Meyer et al 18 , epileptic children and adolescents with refractory seizures, early-onset epilepsy, and developmental retardation seem to be at higher risk for SUDEP. Following this line of reasoning, we reviewed the occurrence of SUDEP in children in our epilepsy unit over an eight-year period 19 . Our study evaluated SUDEP incidence in a cohort of children aged between 0 and 18 years-old, who were evaluated in the Clinical Hospital of Ribeirão Preto in 2000 and followed-up until June, in 2008.…”
Section: Epileptologists Probe Vagus Nerve Stimulation In Children Wimentioning
confidence: 99%
See 1 more Smart Citation